(untitled) (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2014)
Research on exploring effects of Consumer Decision Making Style on Retail Format Choice Behavior and to study the effect of demographic factors on each factor of decision making style was conducted. The usable data of 116 respondents’ was taken from the city of Sukkur in Pakistan. The multiple regression technique was used to explain the role of afore mentioned factors. Results conclude that only 7.9% is explained by Decision Making Styles on Retail Format Choice. And maximum of 18.7% is explained by four demographic factors on a Consumer Decision Making Style.